2018
DOI: 10.1002/jts.22299
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes for Military Veterans With Posttraumatic Stress Disorder: Response Trajectories by Symptom Cluster

Abstract: Although effective posttraumatic stress disorder (PTSD) treatments are available, outcomes for veterans with PTSD are relatively modest. Previous researchers have identified subgroups of veterans with different response trajectories but have not investigated whether PTSD symptom clusters (based on a four-factor model) have different patterns of response to treatment. The importance of this lies in the potential to increase treatment focus on less responsive symptoms. We investigated treatment outcomes by sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Alternatively, reductions in avoidance and hyperarousal symptoms may increase patients’ ability and willingness to engage more fully in trauma memories; thus, reductions in reexperiencing symptoms may follow reductions in other symptom clusters. Consistent with this idea, the results of a recent meta‐analysis demonstrated that reexperiencing symptoms evidenced the smallest effect size across exposure‐based therapy compared to the other symptom clusters and that symptoms further decreased to a significant degree between posttreatment and follow‐up assessments (Phelps et al., 2018). This finding should be explored within other samples of active duty military personnel and other trauma‐exposed populations.…”
Section: Discussionmentioning
confidence: 82%
“…Alternatively, reductions in avoidance and hyperarousal symptoms may increase patients’ ability and willingness to engage more fully in trauma memories; thus, reductions in reexperiencing symptoms may follow reductions in other symptom clusters. Consistent with this idea, the results of a recent meta‐analysis demonstrated that reexperiencing symptoms evidenced the smallest effect size across exposure‐based therapy compared to the other symptom clusters and that symptoms further decreased to a significant degree between posttreatment and follow‐up assessments (Phelps et al., 2018). This finding should be explored within other samples of active duty military personnel and other trauma‐exposed populations.…”
Section: Discussionmentioning
confidence: 82%
“…However, this issue could be tackled through subsequent research endeavors concentrating exclusively on TES or directed towards the isolation of subtypes of PTSD for which NIBS techniques might prove more appropriate. Second, when reported, the types of traumas and time elapsed from the experience of traumatic events were highly dissimilar, which represent, instead, crucial factors for determining the different trajectories of PTSD symptoms and treatment response [ 117 , 118 , 119 , 120 ]. Third, the samples were mostly composed by men, and, in some cases, the sample size was small (e.g., [ 56 , 64 , 66 ]), limiting the generalizability of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…PTSD is associated with intense and extended psychological suffering. The most effective available treatment modality for PTSD—trauma-focused therapy—cannot provide substantial symptomatic relief in the short term (Phelps et al, 2018) and neither can the slow-acting antidepressants, such as the selective serotonin reuptake inhibitors, considered the first-line pharmacological intervention (Akiki and Abdallah, 2019). A single intravenous infusion of a subanesthetic dose of ketamine was found to be associated with a significant and rapid reduction in post-traumatic and depressive symptom severity in patients with chronic PTSD (Feder et al, 2014) and is a promising area of research.…”
Section: Discussionmentioning
confidence: 99%